Research Progress of Compression Heat Pump Coupled with Phase Change Materials for Heat Storage - 杨耿; 肖鑫; 王云峰 (Zhileng xuebao)
In recent years, the research of regenerative heat pump has been widely concerned. The combination of phase change heat storage technology and heat pump can improve the performance of heat pump and the utilization rate of renewable energy, but it still needs further cost reduction and efficiency increase. Therefore, the present study reviews the progress of solid-liquid phase change regenerative heat pumps, and summarizes the applicable conditions and characterization methods of phase change materials applied to heat pumps. The optimization approaches of the performance of the regenerative heat pump system are summarized, including the selection and improvement of phase change materials, the optimal setting of heat exchanger, and the dynamic optimization control strategy of the system. The outstanding performance of regenerative heat pump with cascade heat storage in improving the supply-side comfort and improving the utilization rate of renewable energy indicates the broad prospect of cascade heat storage applied to heat pump energy storage system, and the non-eutectic mixed phase change materials are proposed as alternative materials for cascade heat storage. It is pointed out that it is necessary to summarize and develop new methods to adjust the thermophysical properties of phase change materials for energy storage, so that make the selection and improvement of phase change materials adapt to the optimization research of thermodynamic theory of cascade heat storage device, and further improve the heating decarbonization ability of latent heat storage heat pump.